PROMOTING DIGITAL STORYTELLING AND DICTIONARY TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Yogi Setia Samsi (University of Kuningan, 2016)
This research was aimed at finding whether or not the use of digital storytelling and dictionary can improve students’ vocabulary mastery. To get the answer of the defined research questions, the researcher used quantitative approach and quasi experimental design. The research had been done in SMPN 1 Cilamaya Wetan, and took two classes as sample, namely, 8G and 8H with 40 respondents in each class. There were three steps in this research, namely pre-test, treatment, and post-test. Pre-test was held in both classes to know students’ vocabulary mastery before the treatment. After doing pretest, treatment was held in experimental class by using digital storytelling and dictionary, that used the technology such as infocus, projector, speaker, and LCD in which the materials were taken from youtube, while control class only used song lyrics. In the next step, posttest was held in both classes to know the improvement after the treatment in experimental class. The data of the study were analyzed by using SPSS version 22 for windows. This research findings showed that experimental group had higher vocabulary score than control group. It can be seen from the posttest mean of experimental group was 74.75 , while the mean of control group was 60,62. Meanwhile, the average of normality gained in experimental group was 0.37 and the average of normality gained in control group was 0.075. Thus, the improvement of students’ vocabulary mastery by using digital storytelling and dictionary in experiemental group is greater than using song in control group. It can be concluded that digital storytelling and dictionary improves vocabulary mastery of eight grader of SMPN 1 Cilamaya Wetan.Keywords: vocabulary mastery, digital storytelling, dictionary